iMMUNOTERAPi ALTINDA GELiNEN OTOiMMON HiPOTiROiDi OLGUSU SUNUMU - GÜRSU, Rıza Umar; DEMİR, Gökhan and SERDENGEÇTİ, Süheyla (Cerrahpaşa Medical Journal, 2014)
Background.- lmmunotherapy is one of the current treatment modalities used for the therapy of malignant melanoma and various other malignancies. The immunomodulator agents used for immunotherapy haw different side effects such as autoimmune thyroid dysfunction. Observation.- A case of metastatic malignant melanoma who dewloped autoimmune thyroid dysfunction while under chemoimmunotherapy is presented and the side effects of treatment with immunomodulators are discussed.